Modeling the p3ht Microcavity Reflectance Spectrum: Introducing a Partitioning Scheme for Treating Large Disordered Chromophore Ensembles - Herrera-Urbina, F (AIP Publishing, 2025)
Analysis of the microcavity reflectivity spectrum of a thin poly(thiophene) (P3HT) film is presented, based on the Frenkel-Holstein-Tavis-Cummings Hamiltonian and a Lindblad formalism to describe relaxation through system-bath interactions. A partitioning scheme is employed to treat large, disordered ensembles of P3HT chain segments, which, based on analysis of the free-space absorption spectrum, is divided into aggregate (60%) and amorphous (40%) domains. The reflectivity spectrum is in excellent agreement with the measured spectrum when the ensemble light-matter coupling, root NgS, is taken to be 0.9 eV, where N is the total number of P3HT chain segments (in the aggregate and amorphous domains) and gs is the light-matter coupling for a single segment. The spectrum exhibits a relatively narrow lower polariton (LP) feature with a much broader upper polariton (UP), with an approximate Rabi splitting of 1 eV. The two relatively weak middle polaritons are attributed to bright vibronic polaritons, which owe their spectral appearance to a Herzberg-Teller mechanism in which exciton-phonons with zero quasi-momentum borrow optical intensity from the LP and UP. The spectral feature attributed to the LP originates mainly from aggregate domains, while the UP originates from both aggregate and amorphous domains.